Synthesis and characterisation of nanostructured Co-Pt magnetic films electrodeposited from tartrate-stabilised chloride baths - Teh, Seohhian; Johan, Mohd Rafie; Yaacob, Iskandar Idris (Maney Publishing, 2014)
Cobalt-platinum (Co-Pt) nanocrystalline alloy films were electrodeposited using a novel stable single-bath system containing a complex forming additive which stabilised the Co+2 ions and enhanced codeposition with platinum complexes. The compositions of the electrodeposits was controlled by adjusting the metal ions ratio in the electrolytic bath and by varying the current density. X-ray diffraction results showed that the as-deposited films contained face-centred cubic CoPt3 phase and the calculated crystallite sizes were in nanoscale dimension in a range of 3-10 nm. Scanning electron microscopy results showed formation of granules and clusters. Atomic force microscopy and infinite focus microscopy results showed granular surface morphology and approximately similar surface roughness value on Co43-Pt57 film. Magnetic force microscopy characterisation on Co43-Pt57 showed existence of correlation between magnetic force and surface topography. The saturation magnetisation values of as-synthesised nanostructured Co-Pt films increased with increasing of Co content.